First report of human ehrlichiosis in Turkey - Emiroğlu, Melike; Çelebi, Bekir (The Turkish Journal of Pediatrics, 2019)
Ehrlichiosis, a tick-borne infection, can cause severe and fatal disease. A 6-year-old boy was admitted with fever, chills, malaise, headache, anorexia, rhinorrhoea, and cough lasting two days. He had had contact with a dog 10 days prior, and a tick had been removed the day before. Fever, minimal conjunctival injection, oropharyngeal hyperemia and cracked, hyperemic lips were observed. Laboratory tests were normal except for lymphopenia and hyponatremia. Cytoplasmic morulae in the monocytes and granulocytes were seen on peripheral blood smear. Doxycycline was started immediately, and the fever subsided within 48 hours. Given the Ehrlichia was positive but Anaplasma negative by real-time PCR, he was diagnosed as ehrlichiosis, subspecies identification could not be performed. This is the first human ehrlichiosis case in Turkey.